2014
DOI: 10.1139/cjz-2013-0267
|View full text |Cite
|
Sign up to set email alerts
|

Energy metabolism and cytochrome oxidase activity: linking metabolism to gene expression

Abstract: Modification of mitochondrial content demands the synthesis of hundreds of proteins encoded by nuclear and mitochondrial genomes. The responsibility for coordination of this process falls to nuclear-encoded master regulators of transcription. DNAbinding proteins and coactivators integrate information from energy-sensing pathways and hormones to alter mitochondrial gene expression. In mammals, the signaling cascade for mitochondrial biogenesis can be described as follows: hormonal signals and energetic informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 191 publications
(222 reference statements)
2
4
0
Order By: Relevance
“…We found consistent increases in the activity of mitochondrial enzymes in dwarf white muscle, which argues that “master regulators” of mitochondrial biogenesis may vary among ecotypes and suggests candidates for future studies (reviewed by Bremer et al. ). However, variation in individual protein coding genes may also be important; there is strong evidence for selection on the proximal promoter of the cytoplasmic MDH (Jeukens and Bernatchez ) and the coding regions of many metabolic enzymes (Renaut et al.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…We found consistent increases in the activity of mitochondrial enzymes in dwarf white muscle, which argues that “master regulators” of mitochondrial biogenesis may vary among ecotypes and suggests candidates for future studies (reviewed by Bremer et al. ). However, variation in individual protein coding genes may also be important; there is strong evidence for selection on the proximal promoter of the cytoplasmic MDH (Jeukens and Bernatchez ) and the coding regions of many metabolic enzymes (Renaut et al.…”
Section: Discussionsupporting
confidence: 71%
“…Wild dwarf fish generally express OXPHOS genes in white muscle at higher levels than normal fish (Derome et al 2006;; but see Derome et al 2008), but different subunits of the same enzyme complexes often had different expression patterns, making it difficult to predict the effects of transcriptional divergence on enzyme activity and mitochondrial function. We found consistent increases in the activity of mitochondrial enzymes in dwarf white muscle, which argues that "master regulators" of mitochondrial biogenesis may vary among ecotypes and suggests candidates for future studies (reviewed by Bremer et al 2014). However, variation in individual protein coding genes may also be important; there is strong evidence for selection on the proximal promoter of the cytoplasmic MDH (Jeukens and Bernatchez 2012) and the coding regions of many metabolic enzymes .…”
Section: Ecotypessupporting
confidence: 57%
See 2 more Smart Citations
“…Beck and Fuller (2012) showed that thermal stress induces a decrease in the reserve capacity of the mitochondria (also termed reserve respiratory capacity) in a white bass (Morone chrysops) cell line, which may lead to the development of pathophysiological conditions. In gilthead sea bream (Sparus aurata), thermal stress leads to perturbations of gene expression related to mitochondrial oxidative capacities including COX genes (Bremer et al, 2014), which may be a regulatory response to the temperature-induced increase of oxidative capacities (Bermejo-Nogales et al, 2014). Our study partly supports these reports, since although we reported a sharp temperature-induced decrease in the expression of the cco gene in our perch livers, the activity of the CCO enzyme which increased between 9 and 20˚C, supporting an increase in oxidative capacities, decreased at the higher temperature studied.…”
Section: Temperature Effectsmentioning
confidence: 99%